2007
DOI: 10.1089/jpm.2006.0253
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Caregiver-Perceived Delirium in Patients with Cancer and Generalized Anxiety in their Caregivers

Abstract: Background: Delirium, a common complication of advanced cancer, may put caregivers at risk for poor mental health outcomes. We looked for a relationship between caregiver-perceived delirium in a patient with advanced cancer and rates of caregiver psychiatric disorders.Methods: Using cross-sectional data from 200 caregivers of patients with cancer with a life expectancy of less than 6 months, we determined the frequency of caregiver-perceived delirium, which was defined as caregivers who reported witnessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 45 publications
4
71
0
4
Order By: Relevance
“…Studies of delirium recall and distress have shown that delirium is highly distressing for patients and their caregivers [26,27]. Buss et al [30] found that caregivers for patients with cancer who reported witnessing the patient as "confused, delirious" weekly or more often on the Stressful Caregiving Response to Experiences of Dying (SCARED) were almost ten times more likely to meet criteria for generalized anxiety disorder, after adjusting for caregiver burden and exposure to other stressful patient experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of delirium recall and distress have shown that delirium is highly distressing for patients and their caregivers [26,27]. Buss et al [30] found that caregivers for patients with cancer who reported witnessing the patient as "confused, delirious" weekly or more often on the Stressful Caregiving Response to Experiences of Dying (SCARED) were almost ten times more likely to meet criteria for generalized anxiety disorder, after adjusting for caregiver burden and exposure to other stressful patient experiences.…”
Section: Discussionmentioning
confidence: 99%
“…49,51 In addition to general distress, caregivers of delirious patients have 12 times the risk for being diagnosed with a generalized anxiety disorder. 133 Supporting caregivers through education about delirium has been shown to help reduce these negative impacts. 83 Verbal and written education provides caregivers with a better understanding of delirium, feelings of empowerment, and an enhanced ability to make decisions on behalf of the delirious patient.…”
Section: Family and Caregiver Education And Supportmentioning
confidence: 99%
“…Complications of delirium include longer hospital stays, prolonged cognitive impairment and significant emotional distress to the patient and caregivers [7]. The financial burden of delirium is staggering, totalling more than $16,303 to $64,421 per patient, with direct 1-year health costs estimated to exceed $143 to $152 billion [8,9].…”
Section: Introductionmentioning
confidence: 99%